Development of Google Sites-Assisted E-Module Based on Problem Based Learning Model to Improve Learning Outcomes of Grade XI Students - Amanda, Delvia; Medriati, Rosane; Putri, Desy Hanisa (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to describe the feasibility test of e-modules, improvement of student learning outcomes and student responses to the development of google sites-assisted e-modules based on problem based learning models to improve student learning outcomes. The research method used is Research and Development (R&D) using the ADDIE model, namely Analyze, Design, Development, Implementation, and Evaluation. The subject of the research was grade XI students of SMAN 8 Bengkulu City. The research instruments are observation, interviews, validation questionnaires, and response questionnaires. The results of the study found that the results of expert validation regarding product feasibility tests obtained a percentage of 91% with the "very feasible" category, an increase in student learning outcomes obtained an N-Gain score of 0.76 with the "high" category, and student responses obtained a percentage of 90% with the "very good" category.